Association of 17q22 Amplicon Via Cell-Free DNA With Platinum Chemotherapy Response in Metastatic Triple-Negative Breast Cancer. (2021) - Collier, Katharine A.; Asad, Sarah; Tallman, David; Jenison, Janet; Rajkovic, Andrei; Mardis, Elaine R.; Parsons, Heather A.; Tolaney, Sara M.; Winer, Eric P.; Lin, Nancy U.; Ha, Gavin; Adalsteinsson, Viktor A.; et al.
Abstract : PURPOSE: To determine whether specific somatic copy-number alterations detectable in circulating tumor DNA (ctDNA) from patients with metastatic triple-negative breast cancer (mTNBC) are associated with sensitivity to platinum chemotherapy. MATERIALS AND METHODS: In this secondary analysis of a large cohort of patients with mTNBC whose ctDNA underwent ultralow-pass whole-genome sequencing, tumor fraction and somatic copy-number alterations were derived with the ichorCNA algorithm. Seventy-two patients were identified who had received a platinum-based chemotherapy regimen in the metastatic setting. Gene-level copy-number analyses were performed with GISTIC2.0. Cytobands were associated with progression-free survival (PFS) to platinum chemotherapy using Cox proportional hazards models. The Cancer Genome Atlas and Molecular Taxonomy of Breast Cancer International Consortium data sets were interrogated for frequency of significant cytobands in primary triple-negative breast cancer (pTNBC) tumors. RESULTS: Among 71 evaluable patients, 17q21 and 17q22 amplifications were most strongly associated with improved PFS with platinum chemotherapy. There were no significant differences in clinicopathologic features or (neo)adjuvant chemotherapy among patients with 17q22 amplification. Patients with 17q22 amplification (n = 17) had longer median PFS with platinum (7.0 v 3.8 months; log-rank P = .015) than patients without 17q22 amplification (n = 54), an effect that remained significant in multivariable analyses (PFS hazard ratio 0.37; 95% CI, 0.16 to 0.84; P = .02). Among 39 patients who received the nonplatinum chemotherapy agent capecitabine, there was no association between 17q22 amplification and capecitabine PFS (log-rank P = .69). In The Cancer Genome Atlas and Molecular Taxonomy of Breast Cancer International Consortium, 17q22 amplification occurred in more than 20% of both pTNBC and mTNBC tumors, whereas 17q21 was more frequently amplified in mTNBC relative to pTNBC (16% v 8.1%, P = .015). CONCLUSION: The 17q22 amplicon, detected by ctDNA, is associated with improved PFS with platinum chemotherapy in patients with mTNBC and warrants further investigation.